2011
DOI: 10.1111/j.1365-2516.2011.02500.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of factor VIII gene mutations in patients with severe haemophilia A in Venezuela: identification of seven novel mutations

Abstract: Haemophilia A is caused by mutations in the gene encoding coagulation factor VIII (FVIII). In severe Haemophilia A (sHA), two inversions are responsible for approximately 50% of the genetic alterations (intron 22 and intron 1 inversions). The other mutations are extremely diverse and each affected family generally has its own mutation. Our aim was to detect the genetic alterations present in the FVIII gene (F8) in 54 unrelated male patients with sHA in Venezuela. We initially detected the presence of the intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 32 publications
(49 reference statements)
6
10
0
Order By: Relevance
“…This was achieved through following a protocol that involved up to three procedures: Inv22, Inv1, and F8 sequencing analyses. The frequencies of mutation types in our study are similar to those found in previous studies [7,23,24,25].…”
Section: Discussionsupporting
confidence: 91%
“…This was achieved through following a protocol that involved up to three procedures: Inv22, Inv1, and F8 sequencing analyses. The frequencies of mutation types in our study are similar to those found in previous studies [7,23,24,25].…”
Section: Discussionsupporting
confidence: 91%
“…A total of 61 patients (61%) had a point mutation detected using direct sequencing analyses. The prevalences of missense mutation and small deletion/insertion mutation were 17% and 23%, respectively, which is comparable with those in previous studies . Nonsense and missense mutations were distributed throughout the whole coding sequences of F8 , whereas frameshift mutations were present mainly in exon 14 (74%, 17/23), a hotspot for such mutations, because of the presence of several long polyadenine runs .…”
Section: Discussionsupporting
confidence: 86%
“…Aside from Inv22, the most frequent mutation type resulting in severe hemophilia was point mutation (24.7%, 46 of 186), including missense mutation, nonsense mutation, and splice-site changes; this was followed by small deletion/insertion mutations (15.6%, 29 of 186). The prevalence was compatible with the rates observed in previous studies, [12][13][14] and as expected, all of the null mutations were associated with the severe hemophilia, whereas missense mutations were responsible for all levels of HA severity. Despite using multiple techniques, no mutations were identified in the remaining 7 severe individuals; in these cases, the mutations may have been located deep within introns or in regions outside of F8 that were important for its expression.…”
Section: Mutation Spectrumsupporting
confidence: 91%